(6+2+8+6+3)/5 =(6+10+6+3)/5 =(12+10+3)/5 =(12+13)/5 =25/5 =5 Five is the average of 6, 2, 8, 6, and 3.
(5/6) * (1/10) + (2/3) / (4/11) = (5/6) * (1/10) + (2/3) * (11/4)= (1/12) + (11/6) = 1/12 + 22/12 = 23/12 or 111/12(5/6) * (1/10) + (2/3) / (4/11) = (5/6) * (1/10) + (2/3) * (11/4)= (1/12) + (11/6) = 1/12 + 22/12 = 23/12 or 111/12(5/6) * (1/10) + (2/3) / (4/11) = (5/6) * (1/10) + (2/3) * (11/4)= (1/12) + (11/6) = 1/12 + 22/12 = 23/12 or 111/12(5/6) * (1/10) + (2/3) / (4/11) = (5/6) * (1/10) + (2/3) * (11/4)= (1/12) + (11/6) = 1/12 + 22/12 = 23/12 or 111/12
5+7 = 12 12 times 6 = 72 add the 3 to get 75.
3/4 + 5/6 = 9/12 + 10/12 = 19/12 = 17/12
lcm(3, 5, 8, 4, 6, 12) = 120
(3 + 5 - 6) × 12 = 24.
27÷3+6×5-12= 9+6×5-12= 9+30-12= 39-12= The answer is 27
(6+2+8+6+3)/5 =(6+10+6+3)/5 =(12+10+3)/5 =(12+13)/5 =25/5 =5 Five is the average of 6, 2, 8, 6, and 3.
The first 5 multiples of 3 are as follows: 3, 6, 9, 12, 15
7 + 5 = 12 12 x 6 = 72 72 + 3 = 75 3 + [6 x (5 + 7)] = 75 3 + [6 x 12] = 3 + 72 = 75
Yes, 5/6 is bigger than 3/4. Figure a common denominator is 12, so multiply 3 by 3 (because 4 x 3 is 12) and 5 by 2 (because 6 x 2 is 12) and you get 9/12 (for 3/4) and 10/12 (for 5/6)
3 3/4 + 2 5/6 = 3 9/12 + 2 10/12 = 5 19/12 = 6 7/12 = approx. 6.58
(5/6) * (1/10) + (2/3) / (4/11) = (5/6) * (1/10) + (2/3) * (11/4)= (1/12) + (11/6) = 1/12 + 22/12 = 23/12 or 111/12(5/6) * (1/10) + (2/3) / (4/11) = (5/6) * (1/10) + (2/3) * (11/4)= (1/12) + (11/6) = 1/12 + 22/12 = 23/12 or 111/12(5/6) * (1/10) + (2/3) / (4/11) = (5/6) * (1/10) + (2/3) * (11/4)= (1/12) + (11/6) = 1/12 + 22/12 = 23/12 or 111/12(5/6) * (1/10) + (2/3) / (4/11) = (5/6) * (1/10) + (2/3) * (11/4)= (1/12) + (11/6) = 1/12 + 22/12 = 23/12 or 111/12
5/6 - 3/4 = 10/12 - 9/12 = 1/12.
5+7 = 12 12 times 6 = 72 add the 3 to get 75.
3/4 + 5/6 = 9/12 + 10/12 = 19/12 = 17/12
5/6 + 3/4 = 10/12 + 9/12 = 19/12 = 17/12